The influence of companions and financial influencers on gen z's financial planning: Mediating role of financial literacy - Ketut Vini Elfarosa; Upayana Wiguna Eka Saputra (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2025)
This study investigates the influence of companions and financial influencers on financial planning among Generation Z in Indonesia, with financial literacy serving as a mediating factor, grounded in Social Learning Theory (SLT). Utilizing a quantitative research design and Structural Equation Modeling with Partial Least Squares (PLS-SEM), the research surveyed 170 Indonesian Gen Z individuals, selected via purposive sampling, who actively engaged with financial content on social media platforms. The findings reveal that companion influence significantly enhances financial literacy and financial planning, affirming the role of close social contacts as effective behavioral models. In contrast, financial influencers do not demonstrate a significant direct or indirect effect on financial literacy or financial planning, suggesting that exposure to digital content alone does not ensure effective financial management. Financial literacy is identified as a crucial mediator in the relationship between companion influence and financial planning, while no similar mediation effect is observed for financial influencers. These results underscore the importance of leveraging trusted social networks to improve financial literacy and highlight the need for critical evaluation of influencer content in shaping financial behaviors among young individuals. The study theoretically contributes by validating SLT in financial socialization and practically suggests prioritizing peer-based learning over passive digital content consumption in financial education programs.